STRENGTHENING PRE-SERVICE BIOLOGY TEACHERS' COMPETENCIES IN DEVELOPING HOTS-ORIENTED COGNITIVE ASSESSMENTS THROUGH THE ASSESSMENT LINK APPLICATION AT UNIVERSITI SAINS MALAYSIA - Endang Susantini; Sifak Indana; Rinie Pratiwi Puspitawati; Yuliani Yuliani; Sunu Kuntjoro; Nur Qomariyah; Firas Khaleyla; Rinaldiyanti Rukmana; Muhammad Zahrudin Afnan (LPPM Universitas Flores, 2026)
The growing emphasis on Higher Order Thinking Skills (HOTS) in twenty-first-century education requires pre-service teachers to possess adequate competencies in designing cognitive assessments aligned with the revised Bloom's Taxonomy. However, many pre-service biology teachers continue to experience difficulties in constructing HOTS-oriented assessment items and integrating digital technology into assessment practices. This community engagement program aimed to enhance the competencies of pre-service biology teachers at Universiti Sains Malaysia (USM) in developing HOTS-oriented biology assessment items using the Assessment Link application. The program adopted a participatory, training-based approach integrated with structured mentoring and was implemented through a blended learning model consisting of face-to-face workshops and online mentoring. Program effectiveness was evaluated using pre-test and post-test instruments, participant assignments, observation sheets, and response questionnaires. The findings demonstrated that participants' mean score increased from 59.72 on the pre-test to 71.92 on the post-test, representing an average learning gain of 12.20 points. Participants also demonstrated improved competence in constructing HOTS-oriented biology assessment items and showed positive engagement throughout the training and mentoring activities. The integration of the Assessment Link application facilitated systematic assessment development while strengthening participants' digital assessment literacy. The program concludes that combining HOTS-oriented pedagogical training with digital assessment technology effectively improves pre-service teachers' assessment competencies and provides a sustainable model for teacher professional development in response to the educational demands of the twenty-first century and the Society 5.0 era.